2023
DOI: 10.1038/s41467-023-39388-3
|View full text |Cite
|
Sign up to set email alerts
|

Structure of human CALHM1 reveals key locations for channel regulation and blockade by ruthenium red

Abstract: Calcium homeostasis modulator 1 (CALHM1) is a voltage-dependent channel involved in neuromodulation and gustatory signaling. Despite recent progress in the structural biology of CALHM1, insights into functional regulation, pore architecture, and channel blockade remain limited. Here we present the cryo-EM structure of human CALHM1, revealing an octameric assembly pattern similar to the non-mammalian CALHM1s and the lipid-binding pocket conserved across species. We demonstrate by MD simulations that this pocket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Structural studies have shown that the NT domain of Cx26 and Cx46/50 is folded into the pore, often parallel to the transmembrane segments, against the pore wall, as for other large-pore channels including innexins, pannexin, CALHM, and LRRC8 channels (6,7,(40)(41)(42)(43)(44)(45)(46). However cryo-EM structures of Cx30.1, and Cx43 also show the NT domain separated from the pore wall and lying parallel to the axis of the plasma membrane, thereby narrowing the pore (9, 10).…”
Section: Uncoupling Of Molecule Transport and Atomic Ion Fluxmentioning
confidence: 99%
“…Structural studies have shown that the NT domain of Cx26 and Cx46/50 is folded into the pore, often parallel to the transmembrane segments, against the pore wall, as for other large-pore channels including innexins, pannexin, CALHM, and LRRC8 channels (6,7,(40)(41)(42)(43)(44)(45)(46). However cryo-EM structures of Cx30.1, and Cx43 also show the NT domain separated from the pore wall and lying parallel to the axis of the plasma membrane, thereby narrowing the pore (9, 10).…”
Section: Uncoupling Of Molecule Transport and Atomic Ion Fluxmentioning
confidence: 99%
“…These assemblies are heterogeneous in nature, with paralogs frequently adopting different oligomeric states in the same sample. The smallest assemblies were generally observed for CALHM1, where structures from different species contained between seven and nine subunits ( Demura et al, 2020 ; Ren et al, 2022 ; Ren et al, 2020 ; Syrjänen et al, 2023 ; Syrjanen et al, 2020 ). The size of the respective assemblies is generally larger for other CALHM paralogs, ranging from decamers to tridecamers ( Choi et al, 2019 ; Drożdżyk et al, 2020 ; Liu et al, 2020 ; Syrjanen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 98%
“…These assemblies are heterogeneous in nature, with paralogs frequently adopting different oligomeric states in the same sample. The smallest assemblies were generally observed for CALHM1, where structures from different species contained between seven and nine subunits (Demura et al, 2020;Ren et al, 2022;Ren et al, 2020;Syrjänen et al, 2023;Syrjanen et al, 2020). The size of the respective assemblies is generally larger for other CALHM paralogs, ranging from decamers to tridecamers (Choi et al, 2019;Drozdzyk et al, 2020;Liu et al, 2020;Syrjanen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%